CHRONIC MYELOGENEOUS LEUKEMIA TRANSFORMATION INTO ACUTE LYMPHOBLASTIC LEUKEMIA - Endah Indriastuti; Arifoel Hajat (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
Chronic Myelogenous Leukemia (CML) is a myeloproliferative neoplasm that can progress into various conditions. Transformation of CML into Acute Lymphoblastic Leukemia (ALL) is rare. A 22-year-old male with a history of CML since 2014 and positive BCR-ABL p210 in 2017 came with the complaint of weakness. Physical examination showed hepatosplenomegaly. Complete Blood Count (CBC) showed Hb 7.1 g/dL, WBC 290,620 /uL, platelet 434,000 /uL.Blood Smear Evaluation (BSE) suggested CML blastic crisis with DD of AML-M5. Patient’s condition got worse and the CBC result showed WBC 96,770/uL and platelet 7,000/uL in 2 weeks. Blood smear evaluation was dominated by mononuclear cells with scanty blue cytoplasm, no granules, no Auer rods, loose chromatin, and indistinct nucleoli, suggesting lymphoblasts with a proportion of 60%. The BMA result was dominated by lymphoblast, consistent with ALL. The immunophenotyping result was CD10+, CD34+(0.99%), CD79a+, HLA-DR+, and CD20+. Molecular examination showed positive RUNX1 and NRAS while FLT3, NPM1 and del(5q) was negative.  BCR-ABL gene can be found both in CML and ALL. CML transformation into ALL had been reported to be related with deletion of a transcription gene. Diagnosis of ALL can be established by BMA and immunophenotyping. CD34+ expression of lymphoblast in ALL can be varied and found to be minimal in this case. Patient with history of CML showed an ALL picture based on BSE, BMA, and immunophenotyping suggesting CML transformation into ALL although CD34+ expression was minimal.